2013
DOI: 10.1016/j.taap.2013.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Structurally distinct polycyclic aromatic hydrocarbons induce differential transcriptional responses in developing zebrafish

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous in the environment as components of fossil fuels and by-products of combustion. These multi-ring chemicals differentially activate the Aryl Hydrocarbon Receptor (AHR) in a structurally dependent manner, and induce toxicity via both AHR-dependent and-independent mechanisms. PAH exposure is known to induce developmental malformations in zebrafish embryos, and recent studies have shown cardiac toxicity induced by compounds with low AHR affinity. Unraveling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
56
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 102 publications
13
56
1
Order By: Relevance
“…Though the highest mRNA levels were observed on day 1, the induction was sustained throughout the time course. The high up-regulation of cyp1 genes is in line with previous research (Table S14) (Carney et al, 2006,Goodale et al, 2013,Scott et al, 2011. Also other members of the AhR gene battery were up-regulated (Table S13).…”
Section: Metabolismsupporting
confidence: 91%
See 2 more Smart Citations
“…Though the highest mRNA levels were observed on day 1, the induction was sustained throughout the time course. The high up-regulation of cyp1 genes is in line with previous research (Table S14) (Carney et al, 2006,Goodale et al, 2013,Scott et al, 2011. Also other members of the AhR gene battery were up-regulated (Table S13).…”
Section: Metabolismsupporting
confidence: 91%
“…The ahr gene family is well represented in this group: Several ahr2s were up-regulated on day 1, ahr2a on day 3 as well, and ahr repressor (ahrr) at every time point. The result is in line with previous research showing that ahr2 and ahrr are up-regulated in fish early life stages exposed to AhR agonists (Carney et al, 2006,Goodale et al, 2013. Rainbow trout AHR2α and AHR2β and all members of Atlantic salmon AHR2 protein family are capable of binding TCDD, and may be involved in AhR signaling (Pollenz et al, 2002,Hansson andHahn, 2008).…”
Section: Signal Transduction and Transcriptionsupporting
confidence: 90%
See 1 more Smart Citation
“…This idea is supported by gene microarray studies which have reported the ability of different AhR ligands to not only induce expression of a common set of gene products but to also induce a distinctly different, ligandspecific set of AhR-dependent gene products (21)(22)(23). Ligandspecific modulation of the AhR signaling pathway has been suggested to result from ligand-dependent changes in the AhR which could allow it to interact with different nuclear factors or dimerization partners, to bind to unconventional DREs or unique DNA sequences, and/or to be bound by different coactivators (24)(25)(26)(27).…”
mentioning
confidence: 87%
“…Regarding WFIKKN1, it has been reported to be overexpressed in response to various compounds (Table 3) such as polycyclic aromatic hydrocarbons in zebrafish [54], retinoic acid in human embryonic stem cells [55], the caspase inhibitor RBC1023 [56] in mice and the gastric inhibitory polypeptide in rats [57]. The WFIKKN1 gene is also downregulated in mouse embryonic stem cells overexpressing the N-terminal domain of the Dnmt3a1 DNA methyltransferase probably via epigenetic silencing [58].…”
Section: Wfikkn Expression In Other Tissues or Cell Linesmentioning
confidence: 99%